Kita Dan Dunia Kontemporer (Atau Mengapa Sejarawan Harus Menyesuaikan Cara Kerjanya Dengan Tuntutan Perkembangan Teknologi Informasi Digital) - Agus Suwignyo (SASDAYA: Gadjah Mada Journal of Humanities, 2018)
In the last 15 years, the interest of Indonesian people in the history and study of history has increased very rapidly. This is indicated by the number and various type of historical books sold in bookstores and the posting of different historical events on social media. However, the history taught at school and university lecture does not seem to improve. The efforts of writing and teaching history lessons/courses still focus on models and the results of the formal study which tend to be a state-centric in nature. In particular, historical writing and teaching have faced challenges of the emerging changes caused by the global connectivity of information technology as a historical fact of the contemporary world that is growing. The contemporary world presents a new challenge in the study and teaching of history through the development of digital communications technology. This paper reviews historical positions and historians in the rapid dynamics of the development of digital communications technology. Why and how historians should develop a proper perspective in placing their studies in the current era of digital technology? Papers process data using digital technology and contrast it with the model and approach of historical study in Indonesia so far.